2019
DOI: 10.3390/nu11050975
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrant (Ribes nigrum) Extract Exerts an Anti-Inflammatory Action by Modulating Macrophage Phenotypes

Abstract: Macrophages are polarized into different phenotypes depending on tissue microenvironment where they reside. In obesity-associated inflammation, M1-type macrophages are predominant in the inflamed tissue, exerting pro-inflammatory responses. Our previous studies demonstrate that blackcurrant consumption attenuates hepatic inflammation and lipopolysaccharide-stimulated inflammatory responses of splenocytes in obese mice. In this study, we determined whether blackcurrant modulates macrophage phenotypes to exert i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
3
17
0
1
Order By: Relevance
“…In The present study, HF diet-induced obesity was defined as described in [38] where the degree of obesity is expressed by comparing the body weight (or fat) of the high-fat fed group with control animals ingesting a LF diet; an increase in body weight of 10-25% is defined as moderate obesity. This is similar to that previously reported by our group [12,24,26]. After 6 weeks of respective diets, mice were fasted for 4 h, ip injected with CCK (20 µg/kg) to determine c-Fos expression in hindbrain, and euthanized using deep anesthesia induced with pentobarbital (Fatal Plus, Vortech Pharmaceuticals, Dearborn, MI, USA; 300 mg/kg; i.p.).…”
Section: Animals and Dietssupporting
confidence: 76%
See 1 more Smart Citation
“…In The present study, HF diet-induced obesity was defined as described in [38] where the degree of obesity is expressed by comparing the body weight (or fat) of the high-fat fed group with control animals ingesting a LF diet; an increase in body weight of 10-25% is defined as moderate obesity. This is similar to that previously reported by our group [12,24,26]. After 6 weeks of respective diets, mice were fasted for 4 h, ip injected with CCK (20 µg/kg) to determine c-Fos expression in hindbrain, and euthanized using deep anesthesia induced with pentobarbital (Fatal Plus, Vortech Pharmaceuticals, Dearborn, MI, USA; 300 mg/kg; i.p.).…”
Section: Animals and Dietssupporting
confidence: 76%
“…With the critical roles of the gut microbiota and its communication with the gut-brain axis in the pathogenesis of obesity and metabolic complications, modulation of the gut microbiota composition has been an attractive target to prevent and/or treat those abnormalities [22][23][24]. In particular, since the diet has been associated with critical alterations in the gut microbiota [25], the use of non-invasive dietary approaches such as prebiotics in the presence of HF challenge have been reported to increase beneficial bacteria abundance, decrease local (gut, adipose) and systemic inflammation and preserve vagally-mediated satiety signaling, which is all associated with suppression of adiposity and weight gain [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In obesity-associated inflammation, M 1 -type macrophages are predominant in the inflamed tissue, exerting pro-inflammatory responses. Studies by Lee & Lee (2019) demonstrated that blackcurrant consumption attenuates hepatic inflammation and lipopolysaccharide-stimulated inflammatory responses of splenocytes in obese mice. In this study, we determined whether blackcurrant modulates macrophage phenotypes exert anti-inflammatory action.…”
Section: Resultsmentioning
confidence: 99%
“…The Morus alba extract downregulates the pro-inflammatory molecules P-selectin and fractalkine, decreasing monocytes adhesion to EC [64]. In a recent study, Lee et al demonstrated that anthocyanin-rich blackcurrant extract exerts anti-inflammatory action by repressing the pro-inflammatory M1 polarization of mouse bone marrow-derived macrophages and human THP-1 cells [287].…”
Section: Guaiacols Groupmentioning
confidence: 99%